GERAÇÃO DAS INTERFACES DE USUÁRIO DO SIAMI PARA WEB - COSTA, Bruno Cesar Alves; SASS, Glaucia Gabriel; FACCENDA, Odival; ALVARENGA, Márcia Regina Martins; TEODORO NETO, José Caruzo; Hálex Viotto, GOMES (ANAIS DO ENIC, 2017)
-